In-Vitro Antibacterial Activities Of Ajwa Date Fruit (Phoenix Dactylifera L.) Extract Against Selected Gram-Negative Bacteria Causing Gastroenteritis - Abdullah, N; Ishak, NFM; Shahida, WSW (Int Journal Pharmaceutical Sciences & Research, 2024)
Indexed by WOS